The application of the GLP principles in analytical chemistry - Caroli, Sergio (Henry Stewart Talks, 2013)
Analytical chemistry, Calibration of analytical equipment, Failure of equipment, Hyphenated analytical techniques, Inspections of Good Laboratory Practice-compliant test facilities, Integrity of studies, Maintenance of analytical equipment, Physical-chemical apparatuses, Principles of Good Laboratory Practice, Standard Operating Procedures, Validation of analytical systems